Positive-Strand RNA Viruses Infecting the Red Imported Fire Ant, Solenopsis invicta - Steven M. Valles (Psyche: A Journal of Entomology)
The imported fire ants, Solenopsis invicta and S. richteri were introduced into the USA between 1918 and 1945. Since that time, they have expanded their USA range to include some 138 million hectares. Their introduction has had significant economic consequences with costs associated with damage and control efforts estimated at 6 billion dollars annually in the USA. The general consensus of entomologists and myrmecologists is that permanent, sustainable control of these ants in the USA will likely depend on self-sustaining biological control agents. A metagenomics approach successfully resulted in discovery of three viruses infecting S. invicta. Solenopsis invicta virus 1 (SINV-1), SINV-2, and SINV-3 are all positive, single-stranded RNA viruses and represent the first viral discoveries in any ant species. Molecular characterization, host relationships, and potential development and use of SINV-1, SINV-2, and SINV-3 as biopesticides are discussed.